The effects of three types of dynamic movement, dynamic stretching & preexercise massage warm up on explosive power of elite men Sprint runners - فریبرز هوانلو; فریدون ذبیحی; حمید رجبی; سمانه دامن پاک (فیزیولوژی ورزش و فعالیت بدنی, 2010)
The effects of three types of dynamic movement, dynamic stretching & preexercisemassage warm up on explosive power of elite men Sprint runnersAbstractPurpose: The aim of this study was to compare dynamic movement, dynamic stretching and preexercisemassage protocols on Explosive power of elite sprinters. Methods: Eighteen volunteermale, selected in dynamic movement, stretch and massage groups randomly. In pretest state,athletes ran ten minutes on treadmill and performed both treadmill and specific warm up for 20minute in post test. Margarya-Kalaman test used before and after (first and tenth minutes) protocolsfor explosive power measurement. For data analysis both mixed ANOVA with repeated measuresand one way ANOVA method were used. Results: Results showed that explosive power in threegroups in first minute increased significantly (p<0/05). But this index only in massage wassignificant in tenth minute (p<0/05). Also, explosive power in between dynamic movement andpre-exercise massage groups in first minute differed significantly (p<0/05). But this index didn’tdiffer between groups in tenth minutes significantly (p>0/05). Conclusions: Therefore, dynamicstretching and massage were best interventions (warm up protocols) for explosive power in firstand tenth minute orderly.